Ketepatan Klasifikasi pada Pengelompokan Manajer Proyek Konstruksi Berdasarkan Faktor Pengembangan Sumber Daya Manusia Menggunakan Analisis Diskriminan - Sahadi, Sahadi; Agung Wibowo, M. (Department of Civil Engineering, Diponegoro University, 2014)
The aim of this research is to analyze variables which differentiate big and small construction project manager based on human resources developmental factors and the accuracy of its classification. The result of the research using discriminated analysis approach of 9 variables shows that variables which differentiate big and small construction project manager are leadership, organization climate, organization culture, and job motivation. The accuracy of big and small project manager classification is 83.2 percent, and the rest is caused by other factors.